Optimization of DNA extraction protocols in detecting white spot syndrome virus from shrimp, Penaeus monodon. - Javier, Ma. Carmel F. (2014.)
Using molecular techniques such as Polymerase chain reaction (PCR), the quality of extracted DNA from sample tissues is an important factor for generating product. The extraction process has to isolate purified extracted DNA that is free from all contaminants. This study reports the application of procedures by Caipang et al (2001) and Jaroenram et al (2009) with some modifications in the concentrations of reagent used, centrifugation, incubation and addition of reagents (proteinase K) to extract WSSV-DNA from infected shrimp, Penaeus monodon. Six different DNA extraction procedures were used to extract DNA and compared. The different extraction protocols generated quality DNA which can be used for PCR to detect the presence of WSSV. However differences in the amount of PCR products using the various extraction protocols were observed. The amplification reaction gave strong bands at 232 kb using all protocols except A and C. DNA extraction using 0.05N NaOH plus centrifugation will yield higher and more pure extracted DNS. Generally protocols B and E were the most efficient modified protocols having both considerable concentration and purity of extracted DNA. The least efficient protocol was protocol F having the lowest concentration and lowest purity of extracted DNA. Concentration of NaOH, centrifugation and incubation had significant effects in obtaining extracted DNA in sample tissues with considerably high concentration and purity. Developed methods can be of great use since reagents used are less expensive and this can only be done for a short period of time with less equipments required.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Shrimp; White Spot Sundrome Virus; DNA